Ludwig Wachler als Historiker der deutschen und europäischen Nationalliteratur - Kunicki, Wojciech (Studia Germanica Posnaniensia, 2017)
The article revolves around the research activity of the historian Ludwig Wachler, professor at the University of Wrocław in the years 1815-1838. In his work, Wachler represents the early German patriotism, for which he was subject to police repression. He is shown primarily as a historian of national literature.